Analisis Efisiensi Administrasi Core Tax Administration System (CTAS): Studi Kasus pada PT X - Salma Aqilah; Christian Wiradendi Wolor; Eka Dewi Utari (Master Manajemen, 2025)
This study aims to understand how users perceive the administrative efficiency generated by the use of the Core Tax Administration System (CTAS) at PT X through a qualitative approach. Data was collected through in-depth interviews, direct observations, document studies, and literature reviews. The participants in this study consisted of four employees who actively use the CTAS system in their daily administrative tasks. The findings indicate that CTAS has not yet provided optimal administrative efficiency. This is due to various technical constraints, such as frequent errors, system downtime, and a complicated login process. Additionally, the lack of clear user guidelines makes it difficult for users to adapt. To address these issues, a comprehensive evaluation of the system is needed, along with improvements to the technology infrastructure, the development of more structured technical guidelines, and regular training for users. This study emphasizes the importance of system stability and responsive technical support to ensure the successful implementation of tax administration digitalization.